Impact of a model synovial fluid on supported lipid membranes - Kreuzer, Martin; Strobl, Markus; Dahint, Reiner (Biochimica et biophysica acta. Biomembranes, 2012)
The interaction of a model synovial fluid, here a solution of 3mg/mL hyaluronic acid (HA) in heavy water (D2O), with an oligolamellar stack of lipid (DMPC) membranes on silicon support has been studied by neutron reflectometry and infrared spectroscopy on the molecular scale at non-physiological and physiological conditions. The system under investigation represents a simple model for lipid-coated mammalian joints and other artificial implant surfaces. When exposed to pure D2O at 21°C, i.e. below the main phase transition of the system, the lipid membranes show a lamellar spacing of 65Å. Heating to 26°C results in detachment of all lipid bilayers except for the innermost lipid lamella directly adsorbed to the surface of the silicon support. On the contrary, when incubated in the solution of HA in D2O the oligolamellar lipid system starts swelling. In addition, heating to 39°C does not result in loss of the lipid membranes into the liquid phase. The interfacial lipid coating adopts a new stable lamellar state with an increase in d-spacing by 380% to 247Å measured after 43days of incubation with the model synovial fluid. Potential consequences for joint lubrication and protective wear functionality are considered.